Contribution of Entrepreneurship Pedagogy Learning Model with Production-Based Learning Approach to Entrepreneurs Learning Outcomes in Vocational Higher Education - Hidayat, Hendra; Yulastri, Asmar; ., Ganefri; Sriwahyuni, Diana; Zoni, Ali Akmal (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this study is to describe and test the contribution of entrepreneurship learning pedagogy models with a production-based learning approach to entrepreneurial learning outcomes. This study uses quantitative methods with descriptive correlational. The population was all students who participated in the 2300 people general entrepreneurship courses in higher education, and a sample of 423 students were selected using proportional stratified random sampling. This research tool is a test of entrepreneurial learning outcomes that have been measured for validity and reliability. Data were analyzed using descriptive statistics, and simple regression. The findings of the study show that there is a contribution to the entrepreneurship learning pedagogy model with a production-based learning approach to entrepreneurial learning outcomes in vocational higher education.